ANALISIS BAURAN PEMASARAN UNTUK MENINGKATKAN PENDAPATAN MENURUT PERSPEKTIF BISNIS SYARIAH (Studi kasus pada BUMNag sukatan nagari batu taba, ampek angkek, agam) - Malika Candra Kirana; Sandra Dewi (Jurnal Ekonomi dan Bisnis, 2025)
The importance of increasing the independence and welfare of village communities through economic development, one of which is through the Village-Owned Enterprise (BUMNag). BUMNag is a village economic institution that aims to utilize village resources and assets to build villages and improve community welfare. BUMNag Sukatan Nagari Batu Taba, which had been inactive, was rebuilt in 2022 with two business units: Rumah Pangan and Kios Tani. In an era of increasing business competition, income is the key to business success, which is highly dependent on the marketing strategy implemented. The purpose of this study is to analyze how the marketing mix strategy at BUMNag Sukatan Nagari Batu Taba, Ampek Angkek, Agam to increase business income. This study is a field study with a qualitative method that connects theory with facts using primary and secondary data sources. Data processing and analysis techniques are carried out in three stages, namely data reduction, data presentation and drawing conclusions. Based on the results of the study of the four marketing mixes of BUMNag Sukatan Batu Taba on the price variable meets the very good category, while the product and place variables are included in the good category and the promotion variable is included in the less good category. So for the product variable, it needs to be improved again, especially in the product variation indicator. In the place/location variable, it is necessary to expand product distribution so that it can be more easily reached by consumers. In the promotion variable, it needs to be improved again by using social media to expand market reach. So it can be concluded that in the marketing mix of BUMNag, the Batu Taba gauge on the product, place and location variables need to be improved to increase revenue. From the results of the analysis carried out, the marketing mix applied according to the Islamic marketing concept is halal and thayyib products, flexible pricing, distribution without any elements of coercion, and honest promotions that do not manipulate consumers.